The Relationship between Nursing Service Quality and Patient Satisfaction among Patients Covered by Indonesia’s National Health Insurance Scheme - Palupi, Retno; Yuliani, Eka; Patria, Armen (Genius Journal, 2025)
Introduction: Nursing services are a key determinant of healthcare quality and significantly influence patient satisfaction, especially among BPJS (Indonesia’s National Health Insurance) users. Inadequate nursing care has been associated with low satisfaction levels, impacting service utilization and hospital performance. Objective: This study aimed to examine the relationship between nursing services and patient satisfaction among BPJS users in the polyclinic of Dr. A. Dadi Tjokrodipo Regional General Hospital, Bandar Lampung. Method: A quantitative approach with a cross-sectional design was employed. The population included all BPJS patients in the polyclinic room in 2024. A purposive sampling technique was used to select 99 respondents who met the inclusion criteria. Data were collected using a validated structured questionnaire and analyzed using univariate and bivariate statistical methods, including the Chi-square test. Result: The majority of respondents rated the nursing services as good and expressed satisfaction with the services received. Among those who perceived nursing services as good, most reported being satisfied. Conversely, patients who perceived the services as not good tended to be dissatisfied. A significant relationship was found between nursing services and patient satisfaction (p-value = 0.000). Conclusion: There is a significant association between the quality of nursing services and the level of patient satisfaction among BPJS users. Improving nursing care is essential to enhance patient experiences and promote service utilization. Future studies should explore other contributing factors such as patient feedback, infrastructure, and facility availability to provide a more comprehensive understanding of healthcare quality determinants.